Part IX – September 1968 - Papers - Nickel Induced RecrystaIIization of Doped Tungsten - T. Montelbano; J. Brett; L. Castleman; L. Seigle (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1969)
Impurity-induced low-temperature recrystallization of cold-worked tungsten was inuestigated with emphasis on the influence of nickel on the reaction. Palladium, nickel, aluminum, manganese, platinum, and iron greatly lower the recrystallization temperature of doped tungsten, which zs normally very high, but the recrystallization temperature of electron-be am zone-refined tungsten wzre is slightly raised by conlacl with nickel. Recrystallization can be induced at low temperature by the presence of solid nickel on the surface of doped tungsten wire, but apparently not by exposure to nickel vapors alone. Approximately 200 ppm of Ni dijjused into 10-mil wires at 1200 from a deposit of nickel on the surface produced total recrystallization, whereas more than 600 ppm of Ni could be absorbed frotn a vapor source without altering the fibrous structure of cold-worked tungsten. Once initiated, nickel-induced recrystallization required a continued source of' nickel for propagation of the recrystallization front. The solubility of nickel in fibrous 10-mil W wire was approximalely 500 ppm at 1150' C, and the activation energy for penetration of the recrystallization front was 52 kcal per mole. In many applications the usefulness of tungsten depends on critical control of its structure. Cold-worked tungsten with the fibrous structure developed by suitable thermo-mechanical treatment has a low, but technologically significant, ductility. It has long been known1 that traces of nickel, and perhaps other metals, are profoundly deleterious in doped tungsten, because they induce recrystallization at low temperature, which produces a brittle, equiaxed grain structure. This effect appears to be an exception to the general observation that recrystallization is impeded and the recrystallization temperature raised by the presence of impurities.2"9 Previous studies7-'' of the annealing and recrystallization of tungsten wire have divided the phenomenon into prior recovery stages, primary recrystallization and secondary recrystallization. The present investigation is concerned principally with primary recrystallization which is defined here as the replacement of the fibrous structure of deformed tungsten by equiaxed grains. The objective of this study was to explore the nickel-induced recrystallization reaction in tungsten and attempt to elucidate its mechanism. As well, an effort to define which other elements give rise to low-temperature-induced recrystallization was carried out. EXPERIMENTAL PROCEDURE The procedure adopted for these experiments was essentially to bring nickel and other elements into diffusive contact with cold-worked tungsten wires. The process of recrystallization was followed as a function of time and temperature by light and electron microscopic observations. First the influence of nickel on the recrystallization temperature of arc-melted, zone-refined, and variously doped tungsten wire was determined by electroplating a deposit of nickel on the surface of the wire and annealing at a variety of temperatures for 3 hr. The chemical analyses of the tungsten wires used in this investigation are given in Table I. The surface of the tungsten wire was etched with Murakami's slution' and approximately 0.005 in, of Ni was deposited from a Watts-type low pH bath14 for the conditions of these experiments. Variations in plating thickness from about 0.001 to 0.005 in. had no discernible influence on the resulting structures. The wires were then annealed in an atmosphere of dry hydrogen to establish the recrystallization temperature. Concurrently, un-plated specimens were annealed to establish the recrystallization characteristics of nickel-free wire. The criterion of recrystallization was that the fibrous structure be completely replaced by equiaxed grains after a 3-hr treatment of temperature. This provided more reproducible results than use of the first recrystallized grain or a fixed proportion of re-crystallized structure as the critical observation. The structures encountered in longitudinal and transverse sections were examined by both light and electron microscopy at magnifications up to X32,000 using parlo-dion-carbon replicas shadowed with platinum for the latter method. Second, the influence of a variety of metals on the recrystallization temperature of 0.010 in. D alumina-silica doped tungsten wire, AW136-64, was determined. The elements were applied by electroplating whenever possible. Alternatively, they were vapor-plated on the tungsten wire and a greater thickness built up by coating with a dispersion of metal powder in nitrocellulose lacquer. Elements not amenable to either of these procedures were merely slurry coated on the tungsten. The recrystallization temperature was determined as above. Third, the nickel-induced recrystallization process in doped wire was studied more closely by electroplating 8 mils of Ni on 65-mil alumina-silica doped tungsten wire, AW153-NS10, and exposing the wire to temperatures of llOO°, 1200°, or 1300°C for various times in a hydrogen atmosphere. A circular recrystallization front, 'Onsisting of equiaxed grains, developed at the periphery Of the coated tungsten wire, and the advance of this front into the fibrous interior was studied. These experiments employed relatively coarse 0.065 in. D wire because the 0.010 in. D wire recrystallized too quickly to permit observation of the pene-